2008 Florida Plant Disease Management Guide: Chemical Control Guide for Diseases of Vegetables, Revision No. 19 - Ken Pernezny; Amanda Gevens; Tim Momol; Aaron Palmateer; Natalia Peres; Richard Raid; Pam Roberts; Gary Vallad; Shouan Zhang (EDIS, 2009)
Revised! PPP-6, a 108-page publication by Ken Pernezny, Amanda Gevens, Tim Momol, Aaron Palmateer, Natalia Peres, Richard Raid, Pam Roberts, Gary Vallad, and Shousan Zhang, is a guide to lawful use of sprayable chemicals intended for control of plant diseases affecting vegetables grown in Florida. Published by the UF Department of Plant Pathology, September 2008.